고령화 사회 배경에서 아파트 옥외 휴게 시설 만족도 및 개선 디자인 연구 - 유정정(TingTing Liu); 강재철(Jaecheol Kang) (한국디자인리서치, 2019)
한국의 고령화 비율이 급격히 상승하고 있으며 2026년에는 초고령 사회에 진입할 것으로 전망한다. 이런 배경에서 외부공간의 옥외시설은 노인의 신체적 기능 및 행동적 특성을 고려하여 이미 노후에 들어가거나 곧 노후에 접어들고 있는 다양한 연령 계층의 수요를 충족하도록 디자인해야 한다. 본 논문은 아파트 옥외 휴게 시설에 대한 조사를 2단계로 나누었다. 첫 번째 단계는 부산광역시에서 2010년 이후 지어진 아파트 9채를 편의 표본 추출 방법으로 표본을 추출하여 옥외 휴게 시설을 조사했다. 두 번째 단계는 아파트에 거주하는 65세 이상의 노인을 대상으로 설문조사를 했다. 조사 결과, 옥외 휴게 시설의 고령친화 디자인은 옥외 휴게 시설의 설치 범위, 배치 방향, 휴게 시설의 형태 등을 고려해야 한다. 디자인할 때 안전과 장애인 전용 시설 및 고령친화의 원칙에 따라 아파트 옥외 휴게 시설에 대한 노인의 수요를 전면적으로 충족시켜야 한다. 아파트 옥외 휴게 시설 고령친화 디자인 연구는 향후 새롭게 지을 아파트 옥외 휴게 시설 디자인을 위한 기초 참조 방안으로 활용할 수 있다. The aging rate in South Korea is dramatically increasing and it will develop into the hyper-aged society in 2026. Under the background, design of public facilities should fully consider somatic function and action features of the elderly to make a corresponding design, so as to satisfy the demands of huge groups that have become or will become the elderly. The case study on outdoor rest facilities of apartments can be subdivided into two stages in this thesis. In the first stage, 9 apartments that have been constructed in Busan in 2010 are selected at random to do the field investigation on outdoor rest facilities. In the second stage, the elderly over 65 years old in apartments accept the questionnaire survey. The findings show that it is necessary to do the aging-fitting design from setting range of outdoor rest facilities, chairs’ forms and setting orientation. The design should abide by the principles of security, no barriers and affinity with advance age to satisfy the use demands of the elderly for outdoor rest facilities of apartments. The research achievements for aging-fitting design in outdoor rest facilities of apartments can provide the basic reference scheme for the outdoor rest facility design of apartments in the future. KCI Citation Count: 0